Waterbody type dependence of the spatial distribution of macroinvertebrate communities in temperate China - Yujie Si; Junxia Wang; Junxia Wang; Hongxiang Li; Haonan Li; Ping He; Lei Jin; Cunqi Liu (Frontiers in Ecology and Evolution)
Distance-decay relationships (DDRs) are a useful method for describing the spatial distribution of biological communities. However, the patterns of macroinvertebrate DDRs and the mechanisms of community assembly in continuous lotic-lentic (river-lake) systems remain poorly understood. We compared the spatial and temporal patterns and biogeographic patterns of macroinvertebrate communities in different water types (river vs. lake) in the temperate zone of China. Data were collected from 152 sampling sites in the Daqing River Basin over two years, and multivariate statistical analyses were conducted. These results provide the first description of biogeographical patterns of macroinvertebrate communities in the Daqing River in temperate China. Macroinvertebrates from both the river and lake exhibited contrasting community compositions, likely due to habitat differences. All macroinvertebrate communities showed a significant distance-decay pattern in both waterbody types, with stronger DDRs in the lake. In the lake, spatial and environmental variables contributed to the spatial distribution of macroinvertebrate communities, while in the river, spatial variables were slightly more important than environmental variables. Spatial variables influenced macroinvertebrate community distribution directly and impacted environmental variables indirectly. Importantly, these communities were strongly driven by stochastic processes. Additionally, macroinvertebrate taxa formed ecologically and taxonomically distinct groups, potentially structured by both deterministic and stochastic processes. The normalized stochasticity ratio (NST) quantified the community-building process based on the neutral model, indicating that deterministic processes may dominate in rivers, while stochastic processes may dominate in lakes. The findings highlight the contrasting roles of deterministic and stochastic processes in shaping macroinvertebrate communities in lotic and lentic systems, providing new insights into the mechanisms of community assembly in continuous river-lake ecosystems.